Farmers' credit access in the Democratic Republic of Congo: empirical evidence from youth tomato farmers in Ruzizi plain in south Kivu - Bonnke, S.M.; Dontsop Nguezet, Paul M.; Biringanine, A.N.; Jean-Jacques, M.S.; Manyong, Victor; Bamba, Z. (Informa UK Limited, 2022)
This article assesses the opinions of youth tomato growers on the accessibility of agricultural credit and factors that influence the accessibility in the Democratic Republic of the Congo (DRC). Data originated from a household survey for the 2019/2020 farming season. We interviewed 218 youth tomato growers from 6 horticulture production zones in the South-Kivu, eastern DRC. The result reveals a low rate of 20.6% on accessing agricultural credit among tomato growers. The topmost nature of agricultural credit received was cash-based, mostly from informal sources of finance (92.7%). The findings reveal that the lack of information on agricultural credit, the fear of credit default, and the absence of Microfinance Institutions in the study areas were the highest-ranking factors hindering tomato growers from accessing agricultural credit services. Our probit model shows that total household income, gender, and tomato growers’ membership in a cooperative were essential factors that explain the probability of accessing agricultural credit. We recommend formalising the agricultural credit system by improving agri-finance extension service delivery to associations of tomato growers among the young to access and use agricultural microcredit services effectively to enhance agricultural production, which is a proxy for rural employment creation and poverty reduction.